Pencegahan Perilaku Penyimpangan Anak Melalui Lembaga Layanan Perlindungan dan Pengembangan Anak di Pusat Pengembangan Anak (PPA) Anugerah Pakisan Kabupaten Temanggung - Sutiyono, Eirene Bunga; Faozi, Safik (Universitas Ekasakti, 2023)
Deviant behavior is behavior that violates the moral principles of decency, both in terms of individual humanity and justification as a characteristic of social beings. Not only adults, children also currently show deviant behavior. The current speed of communication flow can foster children's curiosity and encourage them to try new things. The purpose of this study is to explain deviant behavior that often occurs in the environment around PPA and what factors influence children to carry out deviant behavior. In addition, this study aims to explain the efforts made by PPA in preventing deviant behavior in children. This research was carried out using sociological juridical research methods, the specifics of this research are descriptive. The research data was sourced from interviews. Data analysis using qualitative methods. The results of the study (1) factors that influence children to carry out deviant behavior are biological factors, psychological factors, and sociological factors, besides that there are factors from a bad environment, lack of attention from parents and influence from friends. (2) Efforts to overcome deviant behavior in children can be carried out with prevention efforts without punishment, such as the participation of community social institutions. PPA is a community social institution that in responding to children's deviant behavior is by providing infrastructure that accommodates children's creativity, improving children's mental health.